IDENTIFIKASI JENIS SAPONIN DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK METANOL KULIT BATANG SEKILANG (Embelia borneensis Scheff.) TERHADAP BAKTERI Pseudomonas aeruginosa ATCC 9027 DAN Streptococcus mutans ATCC 25175 - Maria F.K. Hayon; Risa Supriningrum; Nurul Fatimah (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Sekilang stem bark (Embelia borneensis Scheff.) contains secondary metabolites, such as alkaloids, flavonoids, tannins, and saponins. Saponin compounds are divided into two types, namely steroids and triterpenoids which have the ability as antibacterial, antifungal, antidiabetic and expectorant. The purpose of this study was to determine the type of saponin and to determine the antibacterial activity of the methanolic extract of sekilang bark against Streptococcus mutans and Pseudomonas aeruginosa bacteria. The research stages included plant determination, sample collection, simplicia making, extract preparation by maceration method using methanol, phytochemical screening, identification of saponins and antibacterial activity test of methanol extract of sekilang stem bark by disc diffusion method against Streptococcus mutans and Pseudomonas aeruginosa bacteria with a concentration of 15% , 20%, 25%, 30%, and 35%. The results showed that the methanol extract of sekilang stem bark contained triterpenoid saponins and had antibacterial activity against Streptococcus mutans bacteria at concentrations of 15%, 20%, 25%, 30%, and 35% with an inhibition zone formed of 7.65 mm, 7.89 mm, 7.67 mm, 7.98 mm, and 7.13 mm the criteria for antibacterial strength were categorized as moderate. The methanolic extract of the bark of sekilang did not show antibacterial activity against Pseudomonas aeruginosa bacteria, because there was no inhibition zone formed around the paper disc. The positive control used was amoxicillin 0.1% and the negative control used 1% DMSO.